2022
DOI: 10.3390/foods11050653
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Ultraviolet Radiation in Fruit and Vegetables: Applications and Factors Modulating Its Efficacy on Bioactive Compounds and Microbial Growth

Abstract: Ultraviolet (UV) radiation has been considered a deleterious agent that living organisms must avoid. However, many of the acclimation changes elicited by UV induce a wide range of positive effects in plant physiology through the elicitation of secondary antioxidant metabolites and natural defenses. Therefore, this fact has changed the original UV conception as a germicide and potentially damaging agent, leading to the concept that it is worthy of application in harvested commodities to take advantage of its be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 148 publications
0
32
0
Order By: Relevance
“…Ultraviolet light (UV) provides a high intensity of light. It has been used in the food industry for several purposes like surface sterilization, fluid disinfestation, air treatment, waste treatment, and insect trapping ( Darré et al, 2022 ). This technology works with a wavelength range of 190–280 nm and results in germicidal and antimicrobial activities used to decontaminate water, fruits, and root vegetables ( Cutler & Zimmerman, 2011 ).…”
Section: New Developed Disinfection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet light (UV) provides a high intensity of light. It has been used in the food industry for several purposes like surface sterilization, fluid disinfestation, air treatment, waste treatment, and insect trapping ( Darré et al, 2022 ). This technology works with a wavelength range of 190–280 nm and results in germicidal and antimicrobial activities used to decontaminate water, fruits, and root vegetables ( Cutler & Zimmerman, 2011 ).…”
Section: New Developed Disinfection Methodsmentioning
confidence: 99%
“…Several research reports suggest that UV light may stimulate the production of phenolic compounds such as ascorbic acid, glucosinolates, or carotenoids in fresh food. These effects keep the attention of researchers ( Darré et al, 2022 ). In this sense, the wavelength approved by the FDA is 254 nm to use in food products and juices (J.A.…”
Section: New Developed Disinfection Methodsmentioning
confidence: 99%
“…It also has use in air disinfection and has been reported to be able to inactivate the human SARS coronavirus. It can also trap insects and facilitate the degradation of unwanted molecules (Darré et al, 2022). Limited reviews on the effects of ultraviolet radiation on microbes exist.…”
Section: Introductionmentioning
confidence: 99%
“…There are four papers within the first topic, dealing with the effect of thermal and non-thermal treatments on whole fruits [ 1 , 2 , 3 , 4 ]. The first study, by Bedrníček et al [ 1 ], investigated the influence of several thermally treated fresh garlic varieties (treated during ageing process—15 days with a temperature gradient ranging from 30 to 82 °C) on the physicochemical parameters of black garlic.…”
mentioning
confidence: 99%
“…It was highlighted that the fresh garlic parameters did not correlate well with the properties of black garlic; therefore, they cannot be used for its quality prediction. The second study, a review by Darré et al [ 2 ], showed that ultraviolet radiation has been found to be a germicide and a potentially damaging agent; however, beneficial properties have also been reported in harvested commodities. UV treatments on whole fruit were shown to induce phytochemicals accumulation, including ascorbic acid, carotenoids, glucosinolates, and, more frequently, phenolic compounds.…”
mentioning
confidence: 99%